Peculiarities of the 7 × 7 to 5 × 5 superstructure transition during epitaxial growth of germanium on silicon (111) surface - Dirko, Vladimir V.; Lozovoy, Kirill A.; Kokhanenko, Andrey P.; Kukenov, Olzhas I.; Korotaev, Alexander G.; Voytsekhovskiy, Alexander V. (Nanomaterials)
This paper presents the results of studying the processes of epitaxial growth of germanium on silicon with crystallographic orientation (111) in a wide temperature range. The temperature dependences of the duration of the transition stage from the 7 × 7 to 5 × 5 superstructure and the values of the critical thickness of the transition from two-dimensional to three-dimensional growth in the range from 250 to 700 ◦C are determined using the reflection high-energy electron diffraction method. It was shown for the first time that the transition time from the 7 × 7 superstructure to 5 × 5 superstructure depends on the temperature of epitaxial growth. The region of low temperatures of synthesis, which has received insufficient attention so far, is also considered.